The Professional Market as Determinant of Medical Missconduct Summary - Perales Cabrera, Alberto (2000)
OBJECTIVES: To describe the phenomenon of corruption in medical professional behaviour and to generate hypothesis to facilitate its scientific study. MATERIAL AND METHODS: Theoretical and descriptive analysis based on documented reports and observational descriptions of the phenomenon within the context of Peruvian reality, interpreted in the light of two paradigmes: Normality (Perales A. et al. 1989) and Personality System (Ortiz R 1994). RESULTS: The following hypothesis is proposed: "The higher medical population density in relation to the work market opportunities the higher risk of medical missconducts, being such a risk higher among physicians with characteristics of greater vulnerability, on account of biological, psychological or social variables". CONCLUSION: The problem of corruption in medical professional conduct must be studied by scientific research methodology in order to establish its dimensions and boundaries, and to identify its causal variables. A working hypothesis is proposed.